Unit Ansor Banser Cyber NU Dalam Melawan Pertumbuhan Katibah Nusantara Di Jawa Timur - Muntaha, Ahmad; Mulyani, Sari; Alexandra, Frisca (Interdependence Journal of International Studies, 2024)
The Katibah Nusantara (KN) group is considered as a radical group that uses the internet to spread its ideology, to recruit members, and to establish a global caliphate. The primary target of the KN group is young people, who are then incited to commit acts of terror, this condition have negative impact in society. Therefore, countering radical islamic ideology through the internet becomes crucial. This research highlights the role of Ansor Banser Cyber Anti Hoax NU Unit in combating the growth of KN ideology in East Java. The research method used is qualitative with a descriptive analytical approach. Data was collected using literature review techniques. The result of this research show that the Ansor Banser Cyber Anti Hoax NU Unit understands that the spread of radical islamic ideology on social media is a threat to the Republic of Indonesia and Pancasila. Several strategies employed include acting as a filter, creating new opinions and serving as a communication bridge.